An Investigation of Key Parameters Affecting the Successful Management of a Knowledge-Based Organizations - SARI, MOHAMMAD HOSSEIN MAHMOUDI (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2019)
This study aims at evaluating the key parameters affecting the success of parent-reliant knowledge-based companies in Iran, considering apparent decline in the rate of knowledge transfer success among the organizations, especially parent-reliant ones. A questionnaire-based investigation was conducted along with social network analysis and financial evidence cross-checking. This research conducts a survey to more than 140 respondents from two dependent and four independent organizations as well as five client companies. After a comprehensive literature review and based on a theoretical framework, we define nine variables for measuring the organizations’ success. We have found that an organization’s success significantly depends on the quantitative and qualitative strength of connections created between a knowledge-based organization and others. Detailed examinations shows that some of the measured variables were affected by the type of the organization. Within this context, success in achieving client satisfaction is considerably different between autonomous and subsidiary companies. We suggest that the way subsidiaries foster a pattern of profitability in business is not the same as that of autonomous organizations. We also discuss key parameters affecting successful management especially regarding connection with others, considering the dissimilarities between self-reliant and dependent knowledge-based organizations.